Penerapan Program Komunitas Literasi 7 Kejora dalam Meningkatkan Potensi Akademik dan Nonakademik Siswa di MA Al-Huda - Amin, Khairul; Matroni, Matroni; Suluh Mardika Alam (CV. Ulil Albab Corp, 2025)
This study aims to analyze the impact of the 7 Kejora Literacy Community Program on the academic and non-academic potential of students at MA Al-Huda. Using a descriptive qualitative method, data was collected through interviews, observations, and documentation over three months. The results indicate that this program successfully enhances students' reading interest, writing skills, and critical thinking abilities. Students’ achievements in poetry competitions and published works illustrate significant development in their literacy skills. Moreover, the program has contributed to improving students’ communication skills, which are essential for interactive learning. These findings align with modern literacy theories emphasizing the integration of critical thinking and communicative abilities in education. This study recommends the continuous development of literacy programs and their implementation in other schools to maximize their positive impact in shaping a literate young generation ready to compete in the information era.